2023
DOI: 10.1002/fsn3.3248
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin/cyclodextrin polymer inclusion complex attenuates ethanol‐induced liver injury by inhibition of DNA damage in mice

Abstract: This study was to examine the protective effects of curcumin/cyclodextrin polymer inclusion complex (CUR/CDP) on ethanol‐induced liver injury in mice and to explore its potential mechanisms. In the ethanol‐induced acute injury mouse model, the effects of pretreatment with silymarin, cyclodextrin polymer (CDP), curcumin (CUR) and CUR/CDP at low, middle, and high doses were evaluated by biochemical and histopathological examination. The liver index, alanine aminotransferase (ALT), aspartate aminotransferase (AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, GSH-PX prevents oxidative damage to cell membranes by catalyzing the breakdown of hydrogen peroxide into water. Both of them work together to maintain the oxidative balance in the organism [ 57 , 58 , 59 ]. To explore the effects of PeCTHC and PeTHC on the levels of antioxidant enzymes, both SOD and GSH-PX were measured in mouse livers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GSH-PX prevents oxidative damage to cell membranes by catalyzing the breakdown of hydrogen peroxide into water. Both of them work together to maintain the oxidative balance in the organism [ 57 , 58 , 59 ]. To explore the effects of PeCTHC and PeTHC on the levels of antioxidant enzymes, both SOD and GSH-PX were measured in mouse livers.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, a study done by Chen et al (2023) revealed that curcumin/cyclodextrin polymer complex (CUR/CDP) can inhibited or down regulated the expression of proteins related to DNA damage, and thereby attenuate liver injury caused by ethanol.…”
Section: Hepatoprotective Activities In Alcoholic Liver Disease (Ald)mentioning
confidence: 99%
“…Evidence has shown that curcumin exhibits anti‐inflammatory, antioxidants, anti‐cancer activities (Khajeh pour et al., 2023 ; Mailafiya et al., 2023 ). These advantageous features are attributed to its elevated antioxidant activity, stemming from the hydroxyl and methylene groups within the β‐diketone moiety present in its chemical structure (Chen et al., 2023 ; Wang et al., 2017 ). There are several studies that explored the positive effects of curcumin on the ovary tissue.…”
Section: Introductionmentioning
confidence: 99%